WEA’s Latest Life Experiment - Jaco Schilp (EXARC, 2012)
Since the last life experiment was in 2001 WEA decided it was time to do another in 2010. The decision was mainly made to give WEA members the opportunity to gain first hand experience in life experiments, for most of the current WEA members had never participated in one. Not every member of the WEA was allowed to participate; such an experiment calls for experienced participants, not in the least because all needed a complete outfit and all necessary equipment made authentically. The period chosen was the Iron Age (900 – 50 BC).